Saliva Droplet Evaporation Experiment and Simple Correlation of Evaporation-falling Curve under Different Temperatures and RH - Dong-Bin Kwak; Hayden D. Fischer; David Y. H. Pui (Aerosol and Air Quality Research)
Abstract In the present study, water and saliva droplet evaporation rates are experimentally evaluated in various environmental conditions: temperature and relative humidity. We found that the ratio of saliva residue size to saliva initial droplet size is 0.216. We also found that the saliva correction factor which is defined as a ratio of water evaporation coefficient to saliva evaporation coefficient was not affected by environmental conditions and was determined as 0.857. By considering the evaporation and gravitational settling effects, the saliva airborne lifetime, i.e., the evaporation-falling curve is numerically calculated and characterized. In addition to this numerical calculation results, we present the simple correlation equation for obtaining the evaporation-falling curve under different temperatures and relative humidity.